Early tracheostomy in patient with severe traumatic brain injury clinical experiences in rural and remote areas - Rosyidi, Rohadi M.; Priyanto, Bambang; Handayani, Aulannisa (International Journal of Research in Medical Sciences, 2018)
Background: Brain injury accounts for most of the causes of death from trauma. Brain injury is defined as a change in brain function, or brain pathology, caused by external forces. Patients with severe brain injury usually required rapid evacuation and special care in the Intensive Care Unit (ICU) room for respiratory control, mechanical ventilation, neurosurgical evaluation, and intracranial pressure monitoring (ICP). During admission to ICU, patients using tracheostomy, because it requires analgesia, sedation, and prolonged ventilation. Methods: Descriptive retrospective study conducted in February and March 2018 at Medical Record Installation of General Hospital Province of West Nusa Tenggara. The sample size is determined by consecutive sampling method. Results: Sample size were 60 people from medical record. Male patient more common than female (90 %). Based on Age more patients are 40 years old (43.3%). More Patient with early tracheostomy was survived (68,33%), and the rest died (31,67%). Conclusions: Severe head injury patients with tracheostomy are common at <18 years and >40 years. Patients with Severe brain injury who get early tracheostomy have more good outcomes, and have relatively short duration of ICU care.